Penerapan manajemen strategi pada bank syariah untuk meningkatkan kepercayaan nasabah - Ummah, Nuril (Maliki Interdisciplinary Journal, 2025)
The implementation of strategic management in Islamic banks is crucial for building and maintaining customer trust amid intense financial industry competition. Strategies grounded in sharia principles emphasize not only performance improvement but also trust, transparency, and social responsibility. Islamic banks must apply digital innovation aligned with ethical standards, enhance human resource quality, and strengthen Islamic organizational culture. The application of good corporate governance and sharia compliance is vital to maintaining credibility and preventing misconduct. This article highlights that synergy between service innovation, open communication, and strong governance serves as the foundation for increasing customer trust and loyalty. Through consistent and sustainable strategic management, Islamic banks can become financially competitive institutions with strong moral and spiritual integrity.